Medical imaging fundamentals, tools and techniques - Jackson, Aaron (Foster Academics, 2016)
This book contains some path-breaking studies in the field of medical imaging. It sheds light on some new techniques and latest advances in this field. Medical imaging refers to the process of visually presenting the interior of a human body for examination and analysis and also to the techniques of monitoring the functioning of the internal organs. It uses the technologies like x-rays, ultrasounds, radiography, endoscopy, etc. This book presents researches and studies performed by experts across the globe. It also includes a detailed explanation of the various fundamentals and tools of medical imaging. It will prove to be a beneficial text for students and researchers in this field.